Spatial Reasoning Construction: The Way to Use It to Solve Geometric Problems - Lingga Nico Pradana; Octarina Hidayatus Sholikhah (Universitas Sriwijaya, 2023)
The aim of this research was to determine the spatial reasoning constructs employed by pre-service elementary school teachers when solving geometry problems. A total of 36 participants were invited to complete an online test, after which two selected individuals were engaged in solving the problems. Interviews were then conducted to accurately describe the process of solving geometric problems. The results showed the existence of two types of spatial reasoning constructions, namely series and parallel. Both construction types revealed the interrelationship between spatial reasoning and the problem-solving process. This research highlighted the significance of spatial reasoning as an integral component in solving geometric problems, emphasizing the need for further investigation into its distinctiveness. This could be achieved by incorporating advanced geometric concepts and materials into future research.